Tudung Ban in Malaysian Hotels: Differing Political Responses - Waikar, Prashant (2017)
The recent controversy surrounding a hotel policy banning the tudung (headscarf) for Malaysia’s frontline hotel staff has elicited responses across the political divide. The statements from various political parties reveal their wider concerns for the upcoming general election.